Beginning Windows Phone App Development - Lee, Henry; Chuvyrov, Eugene (Apress : Imprint: Apress, 2012)
Microsoft's Windows Phone 7 handsets have injected a new vibrancy into the smartphone marketplace and provided bold new opportunities for the Microsoft development community. Take advantage of these opportunities with Beginning Windows Phone App Development, written specifically to help you learn the skills you'll need to develop rich, functional apps for the Windows Phone 7 platform. Authors Henry Lee and Eugene Chuvyrov cover the very latest developments in the field-including the extended APIs offered in the new Mango platform update-so you'll have timely, accurate information at your fingertips. Beginning Windows Phone App Development starts with the basics, walking you through the process of downloading and setting up the right development tools, including Visual Studio,Expression Blend, Silverlight SDK, and Windows Phone SDK. It then takes you step-by-step though the development process as you build and deploy a working application, complete with a sophisticated user interface. Finally, you'll receive step-by-step instructions on packaging and selling your applications through the Windows Phone Marketplace.